Distributed AI, schedules and the semantic web RCal provides a glimpse of what's to come. - Singh, Rahul
Meetings are an integral part of modern life, regardless of whether they're formally established at the workplace or casual agreements made over the phone. Many factors affect meeting scheduling, some of which are explicit (What existing meetings do I have?), implicit (I prefer to avoid meetings before 10:00 am) or cultural (social events should be scheduled for Friday evenings and weekends, but not Sunday mornings).